Barcelona and Madrid : Social Networks of the Avant-Garde. - Ascunce, Aránzazu, 1974- (Bucknell University Press, 2012)
Throughout history, Barcelona and Madrid have competed in practically every aspect of social life, politics, and culture. By delving deep into the myriad of cultural and political complexities that surround these two cities from the onset of Futurism (1909) to the arrival of Surrealism in Spain (1929), a complex social and cultural network is revealed.